Pediatric Boot Camp Series: Obtaining a Consult, Discussing Difficult News - Rebekah Burns; Karen Mangold; Mark Adler; Jennifer Trainor (Association of American Medical Colleges, 2016)
Abstract Introduction Transitioning from medical student to intern requires individuals to possess medical knowledge, clinical skills, and the ability to communicate with a wide variety of health care professional as well as patients and their families. New doctors may be expected to function within the health care team without having received explicit instruction in communication previously. The materials associated with this publication are intended to be used as resources for small-group education of graduating medical students entering into pediatric, family medicine, or emergency medicine residencies. Methods Four pediatric cases serve as the focus points for discussion and role-play around calling consultants and discussing difficult news with families and patients. Brief didactics and detailed facilitator notes help prime learning and guide discussion. The included facilitator notes and slide sets are part of the comprehensive materials necessary to implement this 4-hour course at your own institution. Results This curriculum has been used since 2012 with graduating medical students entering into pediatric, family medicine, and emergency medicine residencies at two institutions within the United States. Feedback has been overwhelmingly positive, and students have reported increased confidence in their ability to communicate with families and other health care providers. Discussion This publication is the second part of a two-part curriculum but may be used independently of the first part. Although the cases are based on pediatrics, the content regarding communication is universal to many medical specialties.